An angiotensin‐converting enzyme (ACE) polymorphism may mitigate the effects of angiotensin‐pathway medications on posttraumatic stress symptoms. Issue 4 (29th April 2015) - Nylocks, K. M.; Michopoulos, V.; Rothbaum, A. O.; Almli, L.; Gillespie, C. F.; Wingo, A.; Schwartz, A. C.; Habib, L.; Gamwell, K. L.; Marvar, P. J.; Bradley, B.; Ressler, K. J.
Abstract : Angiotensin, which regulates blood pressure may also act within the brain to mediate stress and fear responses. Common antihypertensive medication classes of angiotensin‐converting enzyme inhibitors (ACE‐Is) and angiotensin receptor blockers (ARBs) have been associated with lower PTSD symptoms. Here we examine the rs4311 SNP in the ACE gene, previously implicated in panic attacks, in the relationship between ACE‐I/ARB medications and PTSD symptoms. Participants were recruited from outpatient wait rooms between 2006 and March 2014 (n = 3803). We examined the interaction between rs4311 genotype and the presence of blood pressure medication on PTSD symptoms and diagnosis. PTSD symptoms were lower in individuals taking ACE‐Is or ARBs (N = 776). The rs4311 was associated with PTSD symptoms and diagnosis (N = 3803), as the T‐carriers at the rs4311 SNP had significantly greater likelihood of a PTSD diagnosis. Lastly, the rs4311 genotype modified the effect of ACE‐Is or ARBs on PTSD symptoms (N = 443; F1, 443  = 4.41, P  < 0.05). Individuals with the CC rs4311 genotype showed lower PTSD symptoms in the presence of ACE‐Is or ARBs. In contrast, T‐ carriers showed the opposite, such that the presence of ACE‐Is or ARBs was associated with higher PTSD symptoms. These data suggest that the renin‐angiotensin system may be important in PTSD, as ACE‐I/ARB usage associates with lower symptoms. Furthermore, we provide genetic evidence that some individuals are comparatively more benefitted by ACE‐Is/ARBs in PTSD treatment. Future research should examine the mechanisms by which ACE‐Is/ARBs affect PTSD symptoms such that pharmaco‐genetically informed interventions may be used to treat PTSD. © 2015 Wiley Periodicals, Inc.